Detecting thin layer by using different seismic geophones and special processing technique at an archaeological site in southeastern China - Lizan, A.; Tian, G.; Wang, Y.; Chen, R.; Ali, S.; Liu, H. (Геофизический журнал, 2015)
The properties of geophones are important factors for high-resolution seismic exploration and have great influence on data quality. In this study we will address the problems of ultra- shallow seismic data acquisition and processing. The purpose of our study is to evaluate the applicability of using different seismic geophones and processing techniques, to detect a thin soil layer about 20 cm in thickness under the depth of about 2 m in Liangzhu archaeological site, Southeastern China. We have collected seismic data with two kinds of geophones, normal geophones with different natural frequencies inserted into the ground, and towable cable geophones contacting the earth surface. We considered combining the frequency advantages of these two different kinds of geophones to broaden the effective bandwidth of the acquired data. To achieve this, we designed a partial frequency match filtering method in data processing which helps to improve the resolution of seismic reflected data. The result of stacking profiles shows that match filtering is effective in detecting a thin layer compared with drilling samples and other geophysical works.